Effects and Safety of Magnesium Sulfate on Neuroprotection: A Meta-analysis Based on PRISMA Guidelines. Issue 1 (January 2016) - Zeng, Xianling; Xue, Yan; Tian, Quan; Sun, Rong; An, Ruifang
Abstract : Abstract: To evaluate the evidence of effects and safety of magnesium sulfate on neuroprotection for preterm infants who had exposure in uteri. We searched electronic databases and bibliographies of relevant papers to identify studies comparing magnesium sulfate (MgSO4 ) with placebo or other treatments in patients at high risk of preterm labor and reporting effects and safety of MgSO4 for antenatal infants. Then, we did this meta-analysis based on PRISMA guideline. The primary outcomes included fatal death, cerebral palsy (CP), intraventricular hemorrhage, and periventricular leukomalacia. Secondary outcomes included various neonatal and maternal outcomes. Ten studies including 6 randomized controlled trials and 5 cohort studies, and involving 18, 655 preterm infants were analyzed. For the rate of moderate to severe CP, MgSO4 showed the ability to reduce the risk and achieved statistically significant difference (odd ratio [OR] 0.61, 95% confidence interval [CI] 0.42–0.89, P = 0.01). The comparison of mortality rate between the MgSO4 group and the placebo group only presented small difference clinically, but reached no statistical significance (OR 0.92, 95% CI 0.77–1.11, P = 0.39). Summarily, the analysis of adverse effects on babies showed no margin ( P > 0.05). Yet for mothers, MgSO4 exhibited obvious side-effects, such as respiratory depression, nausea and so forth, but there exited great heterogeneity. MgSO4 administered to women at high risk of preterm labor could reduce the risk of moderate to severe CP, without obvious adverse effects on babies. Although there exit many unfavorable effects on mothers, yet they may be lessened through reduction of the dose of MgSO4 and could be tolerable for mothers. So MgSO4 is both beneficial and safety to be used as a neuroprotective agent for premature infants before a valid alternative was discovered.